A BIBLIOMETRIC ANALYSIS OF EFL READING FLUENCY FROM 2016 TO 2021 - Hijril Ismail; Edi Edi (University of Kuningan, 2021)
The aim of the research is to provide an extensive literature review on reading fluency. Articles were located through publish or perish software and the Google scholar database. Scanning by scimagojr.com (Q1, Q2, Q3, and Q4). We analyzed 60 articles from 2016 to 2021. Mendeley software was used to manage and resume the references. We have reviewed this database and attempted to classify articles using VOSviewer software. Four clusters are identified. Cluster 1 consisted of ten items (disability, elementary students, fluency intervention, impact, intervention, reader, reading fluency, reaped reading, student, and teacher), Cluster 2 consisted of seven items word (child, effect, fluency, language, present study, reading, and word), cluster 3 consisted of five items word (comprehension, oral reading fluency, relationship, research, and vocabulary), and cluster 4 consisted of 4 items word (accuracy, development, relation, and study).